National Fund for the Protection of Monuments: legal and financial issues - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
This study deals with the legal and financial issues of the National Fund for the Protection of Monuments (NFOZ), which has been operating since 1 January 2018 as a special purpose fund. The Fund has statutorily assigned revenues that come from fines paid by violators of regulations related to the protection of monuments. The study analyses the fund’s receipts and expenditures listed in its annual financial plans and concludes that, due to its relatively small revenues, the NFOZ contributes only minimally to the financing of the monument protection system in Poland.